INTEGRATION MANAGEMENT OF INDEPENDENT CURRICULUM AND BOARDING SCHOOL CURRICULUM AT MA NURUL ISLAM BAYUNG LENCIR - Sibron, A.; Fauzi, Muhamad; Maryamah, Maryamah; Nisa, Ike Hilatun (Jurnal Asy-Syukriyyah, 2025)
This study examines the integration management of the Merdeka Curriculum and the Pesantren Curriculum at MA Pondok Pesantren Nurul Islam Bayung Lencir. Using a descriptive qualitative approach with a case study design, the study was conducted for six months (August 2024-January 2025) through in-depth interviews, participatory observations, and documentation analysis. The results of the study indicate that the integration of the two curricula has succeeded in creating a holistic education model that combines 21st-century competencies with traditional pesantren values. Integration management is carried out through careful planning, intensive collaboration between educators, ongoing training, and routine evaluations that result in improved learning quality, strengthening the character of students, and developing resources and infrastructure. Despite facing challenges in aligning learning approaches and balancing competencies, MA Nurul Islam has succeeded in developing an adaptive strategy that prepares students with contemporary skills without sacrificing the depth of religious knowledge and noble morals that are the hallmarks of pesantren.